2010
DOI: 10.1038/ncomms1030
|View full text |Cite
|
Sign up to set email alerts
|

Novel survey method finds dramatic decline of wild cotton-top tamarin population

Abstract: For conservation purposes, accurate methods are required to track cotton-top tamarins in their natural habitat. As existing census methods are not appropriate for surveying these monkeys, a lure-transect method combined with playback vocalization was used here to allow accurate counting of the animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 23 publications
0
34
1
9
Order By: Relevance
“…O'Grady et al [36] proposed that population size was the best predictor of extinction risk and was therefore the most cost-effective data to collect on threatened species. Population monitoring is essential to evaluate the success of conservation efforts, yet standard survey methods may be ineffective because animals flee silently before they are seen [15]. Population estimation using a noninvasive genetic census technique does not require visual or physical contact with the individuals, and allow for larger sample sizes to be collected than would be possible with traditional trapping methods [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Grady et al [36] proposed that population size was the best predictor of extinction risk and was therefore the most cost-effective data to collect on threatened species. Population monitoring is essential to evaluate the success of conservation efforts, yet standard survey methods may be ineffective because animals flee silently before they are seen [15]. Population estimation using a noninvasive genetic census technique does not require visual or physical contact with the individuals, and allow for larger sample sizes to be collected than would be possible with traditional trapping methods [24].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used census method is individual counts based on line transects. However, traditional line transect methods do not work well for arboreal primates that tend to flee silently through the forest canopy before being counted [15]. In addition, vegetation can often hamper efforts to spot and count individuals.…”
mentioning
confidence: 99%
“…Our own research has benefited from strong collaborations between statisticians and ecologists, but we note that many researchers do not have the resources that can be taken for granted in academic settings in wealthy countries (Gimenez et al 2013). We have been involved in international collaborations to estimate wildlife abundance and conservation status in countries with little funding for biodiversity monitoring (Moore et al 2010, Savage et al 2010, Lewison et al 2014, Williams et al 2016b and in efforts to help colleagues, particularly students, leverage (i.e. make use of existing but unpublished) historical survey data.…”
Section: Distance Sampling: Assumptions and Challenges For Small-boatmentioning
confidence: 99%
“…Callicebus discolor Dacier et al, 2011), or strip transects (e.g. Saguinus oedipus Savage et al, 2010). Here we focus on the use of playbacks to estimate population densities, though some of the content will be of interest for those using playbacks to survey primate presence.…”
Section: Andrea Salcedo R Manuel Mejia Katie Slocombe Sarah Papworthmentioning
confidence: 99%
“…Although distance sampling requires that individuals do not move in response to playbacks, other methods can still be used. For example, Savage et al, (2010) found that cotton-top tamarins (Saguinus oedipus) are attracted to playbacks of conspecific calls from 150-200m, and so used strip transects and lured individuals to the census line with playbacks.…”
Section: Andrea Salcedo R Manuel Mejia Katie Slocombe Sarah Papworthmentioning
confidence: 99%